Probiotics for Health and Disease - Myth or Truth???? (International Journal of Biomedical and Advance Research, 2014)
Since some decades bacteria known as Probiotics have been supplemented to various foods because of their beneficial effects for human health. The mechanism of action of Probiotics is related to their ability to compete with pathogenic microbes for adhesion sites, to antagonize these pathogens or to modulate the hosts immune response. The potential application of Probiotics for excellent health has recently attracted the attention several teams of investigators. Although only a few clinical studies have been conducted so far, the results to date advocate that Probiotics could be valuable supplement in preventing and treating diseases. This article overviews the currently existing data on the potential benefits of Probiotics for overall health and disease